Determinan Kinerja Pemerintah Desa Sidobinangun Kabupaten Lamongan - Lailatul Mafruhah; Siti Sundari (Journal of Management and Bussines (JOMB), 2023)
This research aims to determine the influence of accountability, competence, internal control and community participation on the performance of the Sidobinangun village government, Deket District, Lamongan Regency. This research collected data through questionnaires distributed to the people of Sidobinangun Village. This study uses analysis in the form of a partial least squares (PLS) model. The conclusion is that the performance of the Sidobinangun village government really requires a high level of accountability and competence from the Sidobinangun village apparatus and is also supported by the high role of the Sidobinangun community, but internal control has not yet had an optimal contribution to the performance of the Sidobinangun village government. Keywords: Accountability, Competence, Internal Control